Blowback [videorecording (DVD)] - Thompson, Bryan G.; Powell, Clifton; McSwain, Marquita (Maverick Entertainment Group, 2026)
A suburban family's perfect world is torn apart when the wife of a former Navy Seal is kidnapped. Ares is forced to turn to his estranged father (a drug kingpin) to help him solve the mystery and save his wife from King's rivals.